Biomechanical Analysis of Mandibular Premolar Restored with Different Custom Post Core - Gavranović-Glamoč, Alma; Jakupović, Selma; Cerjaković, Edin; Topčić, Alan; Berhamović, Emir; Kazazić, Lejla; Strujić-Porović, Sanela; Šehić, Adnan; Bajrić, Elmedin (European Journal of General Dentistry, 2024)
Objective This study investigated biomechanical behavior of custom post core made of six different materials on the tooth with and without the ferrule under different occlusal load.Materials and Methods Three-dimensional models of mandibular first premolar, with and without ferrule, reconstructed from micro-computed tomography image are restored with different custom post core and zirconia crowns. By using the finite element analysis, von Mises stress shown in MPa was measured under simulated axial and oblique load of 200 [N]. To compare the stress distribution, six different custom post core materials were chosen: zirconia, Ni-Cr alloy, gold alloy, glass fiber-polyether ether ketone, polyether ether ketone, and carbon fiber-polyether ether ketone.Results Custom post cores with a higher modulus of elasticity showed higher measured stress in the posts, but less stress in dentin. Measured stress in custom post core under oblique loading was approximately three times higher compared with axial loading. Stress in custom post core and in dentin under both types of loads was slightly higher in teeth without ferrule effect.Conclusion The use of custom cast post cores made of different alloys is recommended in restoration of endodontically treated teeth, with extensive loss of tooth structure especially in teeth without ferrule effect.
Keywords: endodontically treated teeth; custom post core; finite element analysis